When Should Premature Ventricular Contractions Be Considered as a Red Flag in Children with Cardiomyopathy? - Marianna Cicenia; Massimo S. Silvetti; Fabrizio Drago (Journal of Cardiovascular Development and Disease, 2021)
Premature ventricular contractions (PVCs) are common and generally benign in childhood and tend to resolve spontaneously in most cases. When PVCs occur frequently, an arrhythmia-induced cardiomyopathy may be present requiring medical or catheter ablation. PVCs are only rarely the manifestation of a cardiomyopathy. The purpose of this review is to provide some tips and tricks to raise the suspicion of a cardiac disease based on the presence and characteristics of PVCs in children.